1970
DOI: 10.1016/0005-2728(70)90168-4
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chloroplast photosystems 1 and 2 separated by a non-detergent method

Abstract: (u.s.A. SUMMARYClass II spinach chloroplasts were fragmented by passage through the French pressure cell (French press), and the fragments were separated. by fractional centrifugation. Fragments sedimenting between lOQO X g and 10,000 X g (10K) .have a lower chl a/chl b ratio and lower P-700 content than whole chloroplasts.· Fragments -sedimenting between 4o.·ooo x g and 160,000 x g (160K) have a much higher chl a/chl b ratio (6.0) and amuch higher P-700 content (1 P-700/105 chlorophylls) than whole chloroplas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
72
1
1

Year Published

1971
1971
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(85 citation statements)
references
References 19 publications
11
72
1
1
Order By: Relevance
“…If the primary thylakoids in the unfused stacks are comparable to the stroma lamellae of normal chloroplasts, the work of Sane et al (18) suggests that the leaves greened in far red light might be enriched in photosystem 1 activity. Previous low temperature absorption and derivative spectra of chloroplasts and of photosystems 1 and 2 subchloroplast particles obtained by digitonin fractionation showed that the long wavelength forms of chlorophyll, especially the 684, 690, and 698 nm-absorbing forms are associated with photosystem 1 particles (6).…”
Section: Discussionmentioning
confidence: 99%
“…If the primary thylakoids in the unfused stacks are comparable to the stroma lamellae of normal chloroplasts, the work of Sane et al (18) suggests that the leaves greened in far red light might be enriched in photosystem 1 activity. Previous low temperature absorption and derivative spectra of chloroplasts and of photosystems 1 and 2 subchloroplast particles obtained by digitonin fractionation showed that the long wavelength forms of chlorophyll, especially the 684, 690, and 698 nm-absorbing forms are associated with photosystem 1 particles (6).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of the cytb 6 f complexes between the grana and stromal lamellae is much less clear. Biochemical evidence obtained on thylakoids fractionated either mechanically or with the detergent digitonin suggested that cytb 6 f was distributed fairly evenly between the grana and stromal lamellae (Boardman and Anderson, 1967;Sane et al, 1970;Cox and Andersson, 1981;Anderson, 1982;Dunahay et al, 1984). This even distribution was supported by immunogold labeling of the cytb 6 f complex in intact thylakoids and by freezefracture electron microscopy studies comparing the wild type and a cytb 6 f-less mutant of the green alga Chlamydomonas reinhardtii (Allred and Staehelin, 1985;Olive et al, 1986;Vallon et al, 1991;Hinshaw and Miller, 1993).…”
Section: Introductionmentioning
confidence: 88%
“…Photosystem 1 enriched membranes were prepared from isolated thylakoids by Yeda press treatment essentially according to the method of Sane et al (1970). Thylakoid membranes were resuspended in stacking medium (330 mM sorbitol, 5 mM MgCl,, 15 mM NaC1, 50 mM HEPES, pH 7.0) and incubated in the dark at 4 OC for 90 min.…”
Section: Biochemistrymentioning
confidence: 99%